Understanding student resistance as a communicative act - Kim, Jeong-Hee (My University, 2011)
In the current era of “zero tolerance”, disciplinary practices including punishment, expulsion, physical and psychological surveillance, and confinement, are a major part of resistant students’ lived experiences. This article is an ethnographic study of student resistance that is observed in an alternative high school in the U.S., which serves students expelled from regular schools for their acts of resistance. The purpose of this study is to explore how understanding of the meaning of student resistance can be used as a theoretical and pedagogical medium with which teachers can create an equitable, educational milieu that upholds views and experiences of the marginalized students. The study also offers a new insight into resistance theory drawing upon Dewey’s transactional theory of resistance as a communicative act to further suggest what might be possible for the teachers and students to transcend conflicts in order to establish a more meaningful teacher-student relationship, moving beyond zero-tolerance policies.
Keywords: Zero-tolerance policies; Resistance theory; Communicative act; Transactional theory